2011
DOI: 10.1523/jneurosci.4732-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

The RhoGAPcrossveinless-cInteracts withDystrophinand Is Required for Synaptic Homeostasis at theDrosophilaNeuromuscular Junction

Abstract: Duchenne muscular dystrophy is caused by mutations in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…Examples include mutations in the nuclear import gene importin13 (85), in the genes encoding components of the Dystrophin/Dystroglycan protein complex (86), and in genes encoding Rho-GAP/Cdc42-mediated signaling (87); see Reference 13 for a more extensive review of these signaling systems. However, until these signaling systems are tested in the background of a homeostatic challenge, it is not possible to ascribe an activity that is directly related to homeostatic plasticity.…”
Section: Postsynaptic Mechanisms: Scaffolds Sensors and Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include mutations in the nuclear import gene importin13 (85), in the genes encoding components of the Dystrophin/Dystroglycan protein complex (86), and in genes encoding Rho-GAP/Cdc42-mediated signaling (87); see Reference 13 for a more extensive review of these signaling systems. However, until these signaling systems are tested in the background of a homeostatic challenge, it is not possible to ascribe an activity that is directly related to homeostatic plasticity.…”
Section: Postsynaptic Mechanisms: Scaffolds Sensors and Signalingmentioning
confidence: 99%
“…(a) (Left) Cartoon of a synapse with a local calcium domain (red ). Shown are postsynaptic genes implicated in the control of baseline presynaptic release, including those encoding Dystrophin, Distrobrevin(86,110), and Importin13(85). (Right) Following philanthotoxin (PhTx) or glutamate receptor (GluR) perturbation, there is an increase in presynaptic calcium influx (red; 57) and an increase in the readily releasable pool (RRP) of vesicles(51,52).…”
mentioning
confidence: 99%
“…A genetic screen found that cv-c loss-of-function mutations interact genetically with dystrophin mutations in Drosophila wing cross vein formation (Pilgram et al, 2011). Examination of the dystrophin / cv-c genetic relationship at the NMJ showed that postsynaptic loss of cv-c phenocopies dystrophin loss (normal quantal size, and significantly increased quantal content) (Pilgram et al, 2011).…”
Section: Postsynaptic Molecules Regulating Retrograde Increases Inmentioning
confidence: 99%
“…Examination of the dystrophin / cv-c genetic relationship at the NMJ showed that postsynaptic loss of cv-c phenocopies dystrophin loss (normal quantal size, and significantly increased quantal content) (Pilgram et al, 2011). Dystrophin appears to act downstream of Cv-c in the muscle.…”
Section: Postsynaptic Molecules Regulating Retrograde Increases Inmentioning
confidence: 99%
“…The identification of mammalian Dys as a target for phosphorylation by CaMKII is further suggestive, and it is tempting to speculate that Dys mediates negative feedback upon phosphorylation by CaMKII. NMJ localization of Dys depends on the transmembrane protein dystroglycan (Bogdanik et al 2009), and a genetic modifier screen led to the finding that the RhoGAP crossveinless-c and its target Cdc42 act in concert with Dys (Pilgram et al 2011).…”
Section: Gluriia-dependent Synapse Formation and Plasticitymentioning
confidence: 99%